Which factors modulate spontaneous motor tempo? A systematic review of the literature - Desbernats, Anaïs; Martin, Elodie; Tallet, Jessica (Frontiers in Psychology, 2023)
Intentionally or not, humans produce rhythmic behaviors (e.g., walking, speaking, and clapping). In 1974, Paul Fraisse defined rhythmic behavior as a periodic movement that obeys a temporal program specific to the subject and that depends less on the conditions of the action (p. 47). Among spontaneous rhythms, the spontaneous motor tempo (SMT) corresponds to the tempo at which someone produces movements in the absence of external stimuli, at the most regular, natural, and pleasant rhythm for him/her. However, intra- and inter-individual differences exist in the SMT values. Even if several factors have been suggested to influence the SMT (e.g., the age of participants), we do not yet know which factors actually modulate the value of the SMT. In this context, the objectives of the present systematic review are (1) to characterize the range of SMT values found in the literature in healthy human adults and (2) to identify all the factors modulating the SMT values in humans. Our results highlight that (1) the reference value of SMT is far from being a common value of 600 ms in healthy human adults, but a range of SMT values exists, and (2) many factors modulate the SMT values. We discuss our results in terms of intrinsic factors (in relation to personal characteristics) and extrinsic factors (in relation to environmental characteristics). Recommendations are proposed to assess the SMT in future research and in rehabilitative, educative, and sport interventions involving rhythmic behaviors.